Vegetable Revolution and Rural Sustainable Development: A Case Study - Khan, Nizamuddin; Sadiq Salman, Mohammed; Rehman, Anisur (Journal for Geography, 2009)
Indian agriculture is now at a critical juncture. The liberalization of agricultural trade, increasing trends of urbanization and fragmentation of the land have resulted in commercialization of Indian agriculture. In the present scenario, farmers are bound to turn towards more remunerative crops, like vegetables, for their sustenance. India has a large population and diverse agro–climatic conditions that favor the growth of various vegetables in the country. Vegetable revolution, in the last decades, has been a ray of hope for the landless, small and marginal farmers. This has become a new dimension of development in favor of the poor rural masses. Our study was undertaken in the Bulandshahr district, lying in the Indogangetic plain. This area not only has fertile land, but also has an efficient infrastructure to support vegetable cultivation. The present study focuses the role of vegetable cultivation upon rural sustainable development. The study revealed that the area studied witnessed an alarming growth in expansion of vegetable cultivation during recent decades. An efficient vegetable marketing network with the integration of rural markets at a grassroots level is urgently needed for sustainable, economically viable and socially acceptable planning of diversification of agriculture with value added crops like vegetables both in the study area and in the country at a national level.
Keywords: Vegetable revolution; marginal; small farmers; sustainable development